Toward a typology of health-related informal credit: an exploration of borrowing practices for paying for health care by the poor in Cambodia - Ir Por; Jacobs Bart; Meessen Bruno; Van Damme Wim (BMC, 2012)
Abstract Background Borrowing money is a common strategy to cope with health care costs. The impact of borrowing on households can be severe, leading to indebtedness and further impoverishment. However, the available literature on borrowing practices for health is limited. We explore borrowing practices for paying for health care by the poor in Cambodia and provide a typology, associated conditions, and the extent of the phenomenon. Methods In addition to a semi-structured literature review, in-depth interviews were conducted with representatives of 47 households with health-related debt and 19 managers of formal or informal credit schemes. Results A large proportion of Cambodians, especially the poor, resort to borrowing to meet the cost of health care. Because of limited cash flow and access to formal creditors, the majority take out loans with high interest rates from informal money lenders. The most common type of informal credit is locally known as Changkar and consists of five kinds of loans: short-term loans, medium-term loans, seasonal loans, loans for an unspecified period, and loans with repayment in labour, each with different lending and repayment conditions and interest rates. Conclusion This study suggests the importance of informal credit for coping with the cost of treatment and its potentially negative impact on the livelihood of Cambodian people. We provide directions for further studies on financial protection interventions to mitigate harmful borrowing practices to pay for health care in Cambodia.